Simple open-heart surgery protocol for sickle-cell disease patients: a retrospective cohort study comparing patients undergoing mitral valve surgery. (26th August 2022) - Epis, Francesco; Chatenoud, Liliane; Somaschini, Alberto; Bitetti, Ilaria; Cantarero, Fulvio; Salvati, Alessandro Cristian; Rocchi, Daniela; Lentini, Salvatore; Giovanella, Elena; Portella, Gina; Langer, Martin
Abstract: OBJECTIVES: Sickle-cell disease (SCD) patients are considered to be at high risk from open-heart surgery. This study assessed the role of a simple sickling-prevention protocol. METHODS: Perioperative non-specific and SCD-specific morbidity and 30-day mortality are investigated in a retrospective cohort study on patients undergoing isolated mitral valve surgery. Patients with and without SCD were compared. In the SCD cohort, a bundle of interventions was applied to limit the risk of sickling: 'on-demand' transfusions to keep haemoglobin levels of around 7–8 g/dl, cardiopulmonary bypass (CPB) with higher blood flow and perfusion temperature, close monitoring of acid–base balance and oxygenation. RESULTS: Twenty patients with and 40 patients without SCD were included. At baseline, only preoperative haemoglobin levels differed between cohorts (8.1 vs 11.8 g/dl, P < 0.001). Solely SCD patients received preoperative transfusions (45.0%). Intraoperative transfusions were significantly larger in SCD patients during CPB (priming: 300 vs 200 ml; entire length: 600 vs 300 ml and 20 vs 10 ml/kg). SCD patients had higher perfusion temperatures during CPB (34.7 vs 33.0°C, P = 0.01) with consequently higher pharyngeal temperature, both during cooling (34.1 vs 32.3°C, P = 0.02) and rewarming (36.5 vs 36.2°C, P = 0.02). No mortality occurred, and non-SCD-specific complications were comparable between groups, but one SCD patient suffered from perioperative cerebrovascular accident with seizures, and another had evident haemolysis. CONCLUSIONS: SCD patients may undergo open-heart surgery for mitral valve procedures with an acceptable risk profile. Simple but thoughtful perioperative management, embracing 'on-demand' transfusions and less-aggressive CPB cooling is feasible and probably efficacious. Abstract : Sickle-cell disease (SCD) affects more than 30 million people worldwide, with a greater incidence in sub-Saharan Africa (SSA), the Mediterranean Basin, the Middle East and India [1].